(untitled) (The Journal of Forensic Accounting Profession, 2023)
Corruption occurs when there is a misuse of current resources to maximize personal benefits at the expense of other parties, causing financial problems and preventing the development of emerging economies. Forensic accounting services utilize financial data to solve legal disputes. Saudi Arabia’s government does not tolerate obstacles that impede the realization of its ambitious Vision 2030, a long-term plan for transforming society and reforming the economy. The war on corruption has been observed in Saudi Arabian domestic policy. Whether the forensic accounting profession and the readiness of accountants qualified to conduct forensic inquiries and investigations are effectively accompanied by the government’s fight is probed. This study explores the current state of forensic accounting in Saudi Arabia. Potential means of employing such status to make Saudi Vision 2030 a reality to combat corruption and the ability of forensic accounting to ease the government’s fight are also investigated. A questionnaire was conducted on 181 participants comprising accountants, auditors, judges, accountancy academics, Oversight and Anti-Corruption Authority employees, and any supervisory body in Saudi Arabia. The results show that 46% of the surveyed participants were unaware of forensic accounting, implying that despite its significance and demand for its services, forensic accounting is undersupplied in Saudi Arabia. Thus, it is inferred that the current state of forensic accounting is below the required level. To address this issue, forensic accounting should be incorporated into accounting curricula, accountants should join specialized scholarship programs and seek to be certified forensic accountants. Policy-makers must develop charter institutions and related forensic accounting standards. (Previously published on Sciendo: https://sciendo.com/article/10.2478/jfap-2023-0001, pod licencom CC BY-NC-ND 4.0)